Countering Cyberbullying with Hadith: Actualizing Women's Social Ethical Values in the Digital Era - Sahlan Harahap (Yayasan Albahriah Jamiah Indonesia, 2025)
This study aims to explore the actualization of women’s social ethics contained in the hadith as a strategy to counter the phenomenon of cyberbullying and online harassment, which are increasingly rampant in the digital era. The study focuses on understanding the values of social ethics taught by the Prophet SAW, especially those related to respect for women, their rights, and behavioral guidelines in public and private spaces. The methodology used is a qualitative study with a descriptive-analytical approach, involving analysis of relevant hadith texts and literature reviews to understand the modern context. The study’s findings indicate that hadiths discussing respect for women’s honor can be actualized as a guide in designing digital ethics policies, educational programs, and awareness campaigns to prevent cyberbullying and online harassment. In addition, the emphasis on noble morals such as respect, empathy, and protection of human dignity according to Islamic teachings can play a significant role in forming a healthy digital culture. The conclusion of this study confirms the relevance of the teachings of social ethics in the hadith as a long-term solution to address social challenges in cyberspace. The implications include integrating Islamic values into technology policies and public education, especially for the younger generation.